2018
DOI: 10.1097/01.reo.0000000000000113
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Fall Risk of Patients Receiving Hematopoietic Cell Transplant

Abstract: Background and Purpose/Objective: Few studies have examined the efficacy of fall risk assessment tools for patients undergoing hematopoietic cell transplant (HCT). The purpose of this study was to determine whether the Hendrich II Fall Risk Model (HFRM II) can distinguish patients who fell from those who did not fall in the inpatient HCT population. Methods: Observational study. Design: Retrospective chart r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…All six studies were conducted at a single hospital setting with four of the studies conducted in United States (U.S.) hospitals and two in Japan (see Table 2). Four studies took place at an academic medical center (Miwa et al., 2017; Rindflesch et al., 2018; Ueki et al., 2014; Vela et al., 2018), one study was conducted at a U.S. Veterans hospital (Dee et al., 2017), and another was at an urban U.S. hospital with a cancer center (Grady et al., 2020). All articles used retrospective chart reviews to examine the fall risk factor, with three of them including matched controls.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All six studies were conducted at a single hospital setting with four of the studies conducted in United States (U.S.) hospitals and two in Japan (see Table 2). Four studies took place at an academic medical center (Miwa et al., 2017; Rindflesch et al., 2018; Ueki et al., 2014; Vela et al., 2018), one study was conducted at a U.S. Veterans hospital (Dee et al., 2017), and another was at an urban U.S. hospital with a cancer center (Grady et al., 2020). All articles used retrospective chart reviews to examine the fall risk factor, with three of them including matched controls.…”
Section: Resultsmentioning
confidence: 99%
“…The identified risk factors include patient demographics (age of 65 and older), cancer diagnosis (transplant patients with a leukemia diagnosis), symptoms (days of diarrhea, incontinence of urine or stool, increased pulse rate, muscle weakness), medication (hypnotic and anxiolytic medication administration, and recent steroid use), and other factors related to medical treatment (allogenic transplant, post‐engraftment period). For example, patients with allogeneic transplantation have a high risk of fall when compared to patients with oncological conditions receiving other treatments (Miwa et al., 2017; Rindflesch et al., 2018); hypnotic or anxiolytic medications taken post‐transplantation period also increase the risk of fall for patients undergoing BMT (Miwa et al., 2017; Ueki et al., 2014). Ukei (2014) found that falls often occurred in the post‐engraftment period after transplant and were related to symptoms such as dizziness and loss of consciousness, while Vela et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations